REPRESENTASI KETIMPANGAN NILAI SOSIAL DALAM NOVEL “TELUK ALASKA” KARYA EKA ARYANI - Azzahra, Gabrielle Widhan; Hadi, Saptono; Sa'diyah, Lailiyatus; Hermawan, Agus (Universitas Lampung, 2024)
The purpose of this research is to resolve various problems, namely: what social values representations are present in Eka Aryani's novel